Monetary Policy and Alternative Measures of Inflation: Empirical Evidence for the UK - Kučaidze, Karina; Martin, Christopher (Ekonomika, 2015)
The issue of which measure of inflation ought to be targeted by policymakers has been extensively analysed, but the equally important issue of which inflation rate is actually targeted by policymakers in practice has been given much less attention. The paper addresses this question, using data for the UK, a country where differences among the alternative measures are especially marked. We estimate simple Taylor-like monetary policy rules, using several different measures of inflation. We find that plausible models can be obtained for each of the different measures, suggesting that it may not matter which is used in empirical analysis. Models using the RPI measure of inflation have a slight empirical advantage which reflects the ability better to explain monetary policy in more turbulent circumstances.